Peran Family Support Group Terhadap Kekambuhan Pasien Rehabilitasi Narkoba di PLATO Foundation saat Covid-19 - Mutmainatul Ghofar; Sri Widati (LPPM STIKES Muhammadiyah Sidrap, 2022)
Abstract There are many reasons a person decides to abuse drugs. The many reasons of drug abuse can be handled effectively by means of drug addicts getting access to treatment and rehabilitation services according to their individual needs. One of the rehabilitation activities is the Family Support Group. However, in the current state of the covid-9 pandemic, all activities in rehabilitation institutions are certainly not running normally as usual. The purpose of this study was to analyze the role Family Support Group on the recurrence of drug rehabilitation patients at the PLATO Foundation during the covid-19 pandemic. This research is a descriptive study using qualitative data. Intake of research informants using purposive. Collecting data obtained from primary data. Data analysis was carried out using a descriptive research design. The results of this study that Family Support Group activities held by the PLATO Foundation during the COVID-19 pandemic went well. The conclusion of this study is that Family Support Group have an important role in the recurrence of rehabilitation patients during the covid-19 pandemic. Keywords: Family Support Group, Rehabilitation Patients, Relapse.